Recent Trends in Computational Intelligence 2020
DOI: 10.5772/intechopen.91188
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approach to Key Frame Detection in Human Action Videos

Abstract: A key frame is a representative frame which includes the whole facts of the video collection. It is used for indexing, classification, evaluation, and retrieval of video. The existing algorithms generate relevant key frames, but additionally, they generate a few redundant key frames. A number of them are not capable of constituting the entire shot. In this chapter, an effective algorithm primarily based on the fusion of deep features and histogram has been proposed to overcome these issues. It extracts the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Because of the combined elements of human position in movement and the background, detecting representative frames in movies based on human actions is fairly difficult. Gawande et al [2] address the issue and define key frame detection as the process of identifying the video frames that contribute the most to distinguishing the underlying action category from all others. They tested their method on the UCF101 dataset, which is a difficult human action dataset, and found that it can detect critical frames with high accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the combined elements of human position in movement and the background, detecting representative frames in movies based on human actions is fairly difficult. Gawande et al [2] address the issue and define key frame detection as the process of identifying the video frames that contribute the most to distinguishing the underlying action category from all others. They tested their method on the UCF101 dataset, which is a difficult human action dataset, and found that it can detect critical frames with high accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have proposed many pedestrian detection frameworks based on deep learning to improve the accuracy of pedestrian detection [30][31][32][33][34][35]. However, the accuracy of pedestrian detectors is affected by complex backgrounds, pedestrian scale changes, object occlusion, and illumination changes.…”
Section: Literature Surveymentioning
confidence: 99%
“…These pooled frames are used to classify an action. [29] identifies the KFs using CNN and reported precision of 92% in the human action videos. The authors in [30] identify 4 KFs in the sports videos with the help of fully convolutional networks.…”
Section: Motivation and Related Workmentioning
confidence: 99%